Aspiring to Aspirate: L2 Acquisition of English Word-Initial /p/ Over 10 Years - Munro, Murray J.; Derwing, Tracey M.; Saito, Kazuya (Language and speech, 2025)
This short report describes a longitudinal examination of the acquisition of English-aspirated stops by an initial cohort of 24 adult Slavic-language (Russian, Ukrainian, and Croatian) speakers. All had arrived in Canada with low oral English proficiency, and all were enrolled in the same language instruction program at the outset. Initial bilabial stops in CVCs were recorded at eight testing times: six during the first year of the study, again at year 7, and finally at year 10. Intelligibility was evaluated through a blind listening assessment of the stop productions from the first seven testing times. Voice onset times (VOT) were measured for /p/ from all eight times. Mean /p/ intelligibility improved—mainly during a proposed Window of Maximal Opportunity for L2 speech acquisition–but remained below 100%, even after 7 years. For some speakers, early /p/ productions were minimally aspirated, with VOT increasing over time but remaining intermediate between L1 English and L1 Slavic-Language values at 10 years. However, inter-speaker variability was dramatic, with some speakers showing full intelligibility throughout the study and others showing many unintelligible productions at all times. Individual learning trajectories tended to be non-linear and often non-cumulative. Overall, these findings point to a developmental process that varies considerably from one learner to another. It also demonstrates the serious drawbacks of relying on group means to characterize the process of L2 segmental learning.